Dynamic response of an irreversible reaction system to a pulsed perturbation - Albano, Ezequiel Vicente (1999)
The dynamic response of the ZGB surface reaction lattice gas model, for the catalyzed reaction, is studied by means of Monte-Carlo simulations in the neighborhood of its second order irreversible phase transition (IPT). It is found that shortly after driving a stationary configuration into the absorbing state, the relaxation of the system can be well described by a stretched exponential behavior. The dependence of the relaxation characteristic time and the induced changes on the coverage of the reactants, on both, the intensity and the period of the pulsed perturbation, are systematically investigated. The obtained insights can straightforwardly be extended to a wide variety of irreversible systems exhibiting second order IPT's, such as directed percolation, forest fire models, the contact process, branching annihilating walkers, catalyzed reactions, etc.